Pneumonia in bighorn sheep: Risk and resilience. Issue 1 (2nd August 2017) - Cassirer, E. Frances; Manlove, Kezia R.; Almberg, Emily S.; Kamath, Pauline L.; Cox, Mike; Wolff, Peregrine; Roug, Annette; Shannon, Justin; Robinson, Rusty; Harris, Richard B.; Gonzales, Ben J.; Plowright, Raina K.; et al.
ABSTRACT: Infectious disease contributed to historical declines and extirpations of bighorn sheep ( Ovis canadensis ) in North America and continues to impede population restoration and management. Reports of pneumonia outbreaks in free‐ranging bighorn sheep following contact with domestic sheep have been validated by the results of 13 captive commingling experiments. However, ecological and etiological complexities still hinder our understanding and control of respiratory disease in wild sheep. In this paper, we review the literature and summarize recent data to present an overview of the biology and management of pneumonia in bighorn sheep. Many factors contribute to this population‐limiting disease, but a bacterium ( Mycoplasma ovipneumoniae ) host‐specific to Caprinae and commonly carried by healthy domestic sheep and goats, appears to be a primary agent necessary for initiating epizootics. All‐age epizootics are usually associated with significant population declines, but mortality rates vary widely and factors influencing disease severity are not well understood. Once introduced, M. ovipneumoniae can persist in bighorn sheep populations for decades. Carrier females may transmit the pathogen to their susceptible lambs, triggering fatal pneumonia outbreaks in nursery groups, which limit recruitment and slow or prevent population recovery. The demographic costs of disease persistence can be equal to or greater than the impacts of the initial epizootic. Strain typing suggests that spillover of M. ovipneumoniae into bighorn sheep populations from domestic small ruminants is ongoing and that consequences of spillover are amplified by movements of infected bighorn sheep across populations. Therefore, current disease management strategies focus on reducing risk of spillover from reservoir populations of domestic sheep and goats and on limiting transmission among bighorn sheep. A variety of techniques are employed to prevent contacts that could lead to transmission, including limiting the numbers and distribution of both wild and domestic species. No vaccine or antibiotic treatment has controlled infection in domestic or wild sheep and to date, management actions have been unsuccessful at reducing morbidity, mortality, or disease spread once a bighorn sheep population has been exposed. More effective strategies are needed to prevent pathogen introduction, induce disease fadeout in persistently infected populations, and promote population resilience across the diverse landscapes bighorn sheep inhabit. A comprehensive examination of disease dynamics across populations could help elucidate how disease sometimes fades out naturally and whether population resilience can be increased in the face of infection. Cross‐jurisdictional adaptive management experiments and transdisciplinary collaboration, including partnerships with members of the domestic sheep and goat community, are needed to speed progress toward sustainable solutions to protect and restore bighorn sheep populations. © 2017 The Wildlife Society. Abstract : Pneumonia contributed to historical declines of bighorn sheep and impedes population restoration. Management priorities include 1) reducing risk of spillover from domestic sheep and goats 2) facilitating pathogen extinction after spillover has occurred, and 3) exploring options for increasing individual and population resilience in the face of infection.